Efficacy of treatment measures for rabbit passalurosis - Khorolskyi, A.; Yevstafieva, V.; Melnychuk, V. (Scientific Progress & Innovations, 2023)
Helminthes of Passalurus ambiguus species are one of the most common parasites of the intestinal tract of domestic rabbits both on industrial rabbit farms and private farms. The most effective way to treat and prevent passalurosis in animals at present is the use of anti-helminthic preparations, where determining the degree of their anti-parasitic effect is a topical direction of research. This will make it possible to raise the effectiveness of maintaining well-being on rabbit farms and the animals’ timely recovery from this infestation. The purpose of the study was to establish the effectiveness of treatment measures for rabbit passalurosis. The research was carried out on a private farm that was unfavorable as to passalurosis and on the basis of the Laboratory of Parasitology of Poltava State Agrarian University. The therapeutic efficacy of Brovermectin 1 % solution (the active substance is ivermectin), Brovalzen powder (the active substance is albendazole), Albendazole 7.5 % suspension (the active substance is albendazole) was tested in case of rabbit spontaneous passalurosis. It was established that on the 7th day of treatment, the indicators of extense-effectiveness and intense-effectiveness were, respectively: of Brovermectin 1 % – 50.0 and 64.31 %, Brovalzen powder – 70.0 and 82.63 %, Albendazole 7.5 % suspension – 60.0 and 60.9 %. On the 14th day of treatment, Brovalzen powder and Albendazole 7.5 % suspension turned out the most effective preparations for rabbit passalurosis, where the indicators of their extense-effectiveness and intense-effectiveness reached 100.0 %. A lower therapeutic effectiveness was registered when using Brovermectin 1 % solution, which was injected to diseased animals. Its extense-effectiveness and intense-effectiveness made 60.0 and 80.9 %, respectively. Moreover, the indicators of the intensity of passalurous invasion on the 7th and 14th day of treatment were at the level of 4.20±1.27 and 2.50±0.75 eggs, and the indicators of the prevalence of passalurous infection were 50.0 and 40.0 %, respectively. The obtained results of experimental studies allow recommend anti-helminthic oral preparations of domestic production Brovalzen powder and Albendazole 7.5 % suspension for effective treatment and prevention of rabbit passalurosis.